The effect of repetitive transcranial magnetic stimulation (rTMS) on symptoms in obsessive compulsive disorder. A randomized, double blind, sham controlled study - Prasko, Ján; Pasková, Beata; Záleský, Richard; Novák, Tomás; Kopecek, Miloslav; Bares, Martin; Horácek, Jirí (Neuro endocrinology letters, 2006)
BACKGROUND: The goal of our study is to assess whether transcranial magnetic stimulation (rTMS) would facilitate the effect of antidepressant in OCD patients. METHOD: The aim of the randomized, double-blind, sham controlled study was to compare the 2 and 4 week efficacy of the 10 sessions rTMS with sham rTMS in serotonin reuptake inhibitor resistant OCD patient. Thirty three right-handed patients were randomly assigned to either active rTMS or to sham rTMS. Active rTMS with the frequency of 1 Hz at 110% of motor threshold (MT) was administered over the left dorso-lateral prefrontal cortex. The same time schedule was used for sham administration. Thirty patients finished the study, three patients' dropped out at the beginning. Psychopathology was assessed by CGI, HAMA, Y-BOCS and BAI before the treatment, immediately after the experimental treatment, and 2 weeks after the experimental treatment by an independent reviewer. RESULTS: Both groups improved during the study period but the treatment effect did not differ between them in any of the instruments. CONCLUSION: Low frequency rTMS administered over the left dorso-lateral prefrontal cortex during 10 daily sessions did not differ from sham rTMS in facilitating the effect of serotonin reuptake inhibitors in OCD patients.
Keywords: elektrostimulační terapie; výsledek terapie; kombinovaná terapie; Prefrontal Cortex; Selective Serotonin Reuptake Inhibitors; Drug Resistance; Male; obsedantně kompulzivní porucha; Combined Modality Therapy; Paroxetine; Serotonin Uptake Inhibitors; Obsessive-Compulsive Disorder; Electric Stimulation Therapy; transkraniální magnetická stimulace; neparametrická statistika; Statistics, Nonparametric; Transcranial Magnetic Stimulation; prefrontální mozková kůra; Adult; selektivní inhibitory zpětného vychytávání serotoninu; dospělí; mužské pohlaví; léková rezistence; Severity of Illness Index; antidepresiva druhé generace; dvojitá slepá metoda; Neuropsychological Tests; Treatment Outcome; lidé; ženské pohlaví; Humans; paroxetin; neuropsychologické testy; stupeň závažnosti nemoci; Double-Blind Method; Female; Antidepressive Agents, Second-Generation